Las herramientas tecnológicas como recursos motivacionales en el proceso de enseñanza-aprendizaje de la especialidad informática del 2do y 3er año de bachillerato del Colegio Dr. Modesto Chávez Franco, de la ciudad de Santa Rosa, período lectivo 2012-2013. - Santín Aguila, Eduardo Javier (2013)
The use of technological tools in the teaching-learning process are designed to facilitate the work, exchanging information and knowledge within and outside the classroom. The information technology and communication have transformed the education system being these indispensable in learning.